Creative Economic Subsector Mapping in Central Bangka District and its Resistance in the Covid-19 Pandemic - I Gede Wyana Lokantara; Dessy Mayasari; Farisa Maulinam Amo (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2022)
The Covid-19 pandemic has harmed the sustainability of economic activities in Indonesia. Central Bangka Regency, the Covid-19 pandemic, has also harmed business actors. The purpose of this study was to analyze the mapping of the creative economy sub-sector in Central Bangka Regency and its survival during the Covid-19 pandemic.Â  This study uses a mixed-method analysis approach. Quantitatively, this analysis uses linear regression analysis to identify the influence of government policies on the survival of creative economy businesses during the pandemic. Qualitative analysis is carried out by identifying data on the distribution of the creative economy that still persists during the pandemic and the factors that influence it both internally and externally using the Quantitative Strategic Planning Matrix (QSPM). The results of the analysis obtained are the weighted IFE value of 2.350 and the weighted EFE value of 2.756 which can be plotted in the Internal-External matrix. This shows that the creative economy business in Central Bangka Regency is currently in a period of growth because it previously experienced a reduction in production and distribution during the Covid-19 Pandemic. Meanwhile, based on the results of the QSPM analysis, the main strategy that must be carried out during this pandemic is to strengthen promotions using the digital marketing concept. Meanwhile, based on the results of linear regression analysis, it was found that there was a positive relationship between the survival of the creative economy business during the pandemic and the creative economy management program in the Central Bangka Regency.